2021
DOI: 10.1504/ijse.2021.113318
|View full text |Cite
|
Sign up to set email alerts
|

Credit access and the performance of non-farm household enterprises: evidence from Nigerian data

Abstract: Inadequate availability of credit access is one of the major problems facing household enterprises in developing countries, especially Nigeria. Despite various government interventions aimed at solving this problem, it is still perceived that credit access is a serious challenge facing these enterprises in Nigeria. Hence, this study examined the impact of credit access on the performance of total stock of input supply of non-farm household enterprises in Nigeria. Unlike the bulk of existing studies, we employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 17 publications
(26 reference statements)
2
10
0
Order By: Relevance
“…These findings are interesting because these two factors would likely worsen in the aftermath of the ongoing Covid-19 pandemic. In Nigeria, Ojonta and Ogbuabor (2021) demonstrated that the pandemic has severely impacted on households and businesses. The evidence that has emerged from this study suggests that for NHEs to contribute towards growth and development in Nigeria on a sustainable basis in the post Covid-19 era, there is a need for government to frontally address the challenge of access to credit facing these enterprises.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings are interesting because these two factors would likely worsen in the aftermath of the ongoing Covid-19 pandemic. In Nigeria, Ojonta and Ogbuabor (2021) demonstrated that the pandemic has severely impacted on households and businesses. The evidence that has emerged from this study suggests that for NHEs to contribute towards growth and development in Nigeria on a sustainable basis in the post Covid-19 era, there is a need for government to frontally address the challenge of access to credit facing these enterprises.…”
Section: Resultsmentioning
confidence: 99%
“…These studies generally established that access to credit impacts positively and significantly on the performance of enterprises. Some studies (e.g., Lam et al, 2019;Jimi et al, 2019) found that access to credit is an important driver of agricultural productivity, while others (Ojonta and Ogbuabor, 2021;Nwosu et al, 2018) showed that credit access enhances labour allocation patterns, total factor productivity, technology adoption, and business efficiency.…”
Section: B Empirical Literaturementioning
confidence: 99%
See 3 more Smart Citations